APLIKASI ACCELEROMETER 3 AXIS UNTUK MENGUKUR SUDUT KEMIRINGAN (TILT) ENGINEERING MODEL SATELIT DI ATAS AIR BEARING - Haryanti, Munnik; Kusumaningrum, Nurwijayanti (Universitas Tarumanagara, 2008)
This paper described of design of accelerometer application to measurement of tilt of engineering model of satellite. One of test satellite is how to control the satellite attitude, how to reduce the disturb. The satellite placed on the air bearing where it can free move like on the outer space. The satellite give a disturb until the attitude is change, where one of attitude is change is tilt. From the tilt the user can analyses and gave a command what to do. We use accelerometer type LIS3L06AL to sense a tilt. This sensor has sensitivity 0.66 V/g. The accelerometer placed on the air bearing where one of axis across with the earth. This condition, the accelerometer will force 1 g. If the accelerometer position is change, the accelerometer will act force 1 g times sin Î¸.